REPERCUSSIONS FROM THE USE OF CRACK IN DAILY FAMILY LIFE - Daiana Foggiato de Siqueira; Claudete Moreschi; Dirce Stein Backes; Valéria Lerch Lunardi; Wilson Danilo Lunardi; Camila Biazus Dalcin (Universidade Federal do Paraná, 2012)
The aim was to know the repercussions of crack cocaine use in daily family life. The Grounded Theory method was used, conducted through in-depth interview, with 15 family members of drug users who were admitted to a hospital detoxification unit in the central region of Rio Grande do Sul between May and December 2010. Once analyzed, the data resulted in the main category Living in conditions of uncertainty and in the subcategories Contextualizing the crack cocaine phenomenon in the family environment; Perceiving the causes of the battle for survival; Demonstrating the positive and negative intervenient factors; and Facing the consequences. It is concluded that crack cocaine users' family members feel uncertainty, guilt, all kinds of fears, and helplessness in the face of the unexpected. It is necessary to rethink how health professionals should be and act, recognizing the uncertainties, chaos and contradictions lived through by these family members